Persepsi Penyuluh Terhadap Strategi Komunikasi dalam Pemanfaatan Media Informasi di Era Digital di Kabupaten Kebumen - Saridewi, Larasati Puspita; Wiguna, Rila Bekti (LP3M Universitas Putra Bangsa, 2023)
Delivering information in agricultural extension requires a special strategy by considering various elements in agricultural extension. One of the communication strategies used by agricultural instructors in this digital era is by utilizing social media, where instructors convey their communication material through various media, both traditional and modern. The aim of this research is to describe the perceptions of instructors in the use of digital technology in delivering extension services. The research used a survey method with a sampling technique using simplified random sampling consisting of 60 extension workers. Data analysis to measure instructors' perceptions of instructors' communication strategies in using digital media was carried out by calculating scores. The results of the research show that the communication strategies used by extension workers in delivering education to farmers can be applied so that farmers can carry out internal communication activities using digital media more efficiently and effectively in conveying recommended recommendations in farming. Extension workers have a positive perception of communication strategies in the use of information which is demonstrated through communication techniques, communication channels, communication messages and use of the internet. The instructor's perception is in the medium criteria where the instructor is quite good in carrying out his communication activities.